Color Stability of Different Aesthetic Archwires (An In vitro study) - Zainab Th Noori; Nidhal H Ghaib (College of Dentistry/ University of Baghdad, 2016)
Background: Coated aesthetic archwires are currently the existing solutions for the esthetic problem, but the color of these archwires tends to change overtime. This study was aimed to evaluate the color stability of different types of esthetic archwires from four different companies at different time periods after immersion of two different staining drinks which are tea and Pepsi cola. Materials and methods: 48 specimens were prepared, each specimen contains 10 aesthetic archwires; and were divided according to type of solution into two groups: A (tea) &B (Pepsi cola); each group contained 24 specimens (12 specimens were immersed in the staining solution as 4 specimens for each time intervals and 12 specimens were immersed in distilled water as control group). Each subgroup contains one specimen from each company. Color measurements were performed by means of a computed spectrophotometer according to the Commission Internationale de I'Eclairage L*a*b* system, and color changes (ΔE*) and National Bureau of Standards units. Results: Both staining solution caused color change in variable degree and the higher amount of color instability was found for the archwires from the Hubit Company while the least amount of color change was for the archwires from the Orthotechnology Company. Conclusion: The tea caused highly significant change on the aesthetic archwires which is higher than the effect of the Pepsi cola. Key words: Color stability, aesthetic archwires, staining drinks.